Ali je umetna inteligenca inteligenca v pravem pomenu besede? - Žalec, Bojan (Bogoslovni vestnik, 2023)
The central question of the article is already formulated in the title. The author advocates a minimal definition of intelligence: intelligence is independent problem solving. The level of intelligence depends on the complexity of the problems and the degree of independence in solving them (Klaus Mainzer). According to this definition, the author notes that intelligent machines already exist. These are AI systems that are capable of deep learning. In the paper, the author presents criticisms of the claim that AI is intelligent in the literal sense and not just in the metaphorical sense. These criticisms are based on objections that can be divided into two basic groups. Proponents of the first line of criticism cite mental abilities (such as phenomenal consciousness and awareness) and aliveness as essential attributes of intelligence, rejecting the notion of artificial life as nonsense. Inanimate and non-mental systems are merely adaptive, not intelligent systems. Representatives of the second group claim that the indispensable characteristics of intelligence are generality, intuition, common sense and abduction. The author analyses the aforementioned criticisms and concludes that their proponents have not given good reasons against the minimal definition.
Keywords: attribution of intelligence to artificial intelligence; definicija inteligence; definition of intelligence; generality; independent problem solving; mental attributes; pripisovanje inteligence umetni inteligenci; psihični atributi; samostojno reševanje problemov; splošnost